Compatibility Rate of Clinical and Histopathologic Diagnosis of Oral Lesions in Zahedan Dental School during 1999-2015 - Shirin Saravani; Mahya Tavakoli Amin; Hamideh Kadeh (Mashhad University of Medical Sciences, 2016)
Introduction: Different oral lesions have clinical characteristics which in some cases are similar. Therefore, in these cases histopathological examination for correct diagnosis is necessary. The aim of this study was to evaluate the compatibility rate of clinical and histopathological diagnosis of oral lesions in Zahedan School of dentistry. Methods: In this retrospective study, determination of the compatibility of clinical and histopathological diagnosis was done using 631 available records in department of pathology, Zahedan School of dentistry, during 1999- 2015. Type of the lesions (neoplastic and non-neoplastic), and demographic data including age, gender, location of lesions (intraosseous or soft tissue), and clinician's specialty was extracted from patients records and data were analyzed using SPSS (V.21) software and Chi- Square test. Results: Total compatibility rate between clinical and histopathological diagnosis was 70.1%. The most accurate clinical diagnosis was related to lichenoid lesions (100%) and leukoplakia (100%) and verrucous carcinoma had the least diagnostic compatibility (20%). There was no significant relationship between compatibility of histopathological and clinical diagnosis with age range, gender, location, and clinician's specialty. Also non-neoplastic lesions with compatible histopathological and clinical diagnoses were three times more than neoplastic lesions. (P=0.03). Conclusion: Although there was a great compatibility between clinical and histopathological diagnosis, many records had no clinical diagnosis and the inconsistency was also significant. Therefore, more attention to clinical signs and effective cooperation between the clinician and pathologist for correct and more accurate diagnosis and treatment is recommended